De Verkeerde K(r)ant. (Eindhoven : De Roze Driehoek, 1980)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : PB 7665, 5601 JR Eindhoven
Nummer 35 bevat een audiocassette
Nederlands
Periodiek